Cancer-Associated Fibroblast Heterogeneity, Activation and Function: Implications for Prostate Cancer - Jasmine S. Owen; Aled Clayton; Helen B. Pearson (Biomolecules, 2022)
The continuous remodeling of the tumor microenvironment (TME) during prostate tumorigenesis is emerging as a critical event that facilitates cancer growth, progression and drug-resistance. Recent advances have identified extensive communication networks that enable tumor–stroma cross-talk, and emphasized the functional importance of diverse, heterogeneous stromal fibroblast populations during malignant growth. Cancer-associated fibroblasts (CAFs) are a vital component of the TME, which mediate key oncogenic events including angiogenesis, immunosuppression, metastatic progression and therapeutic resistance, thus presenting an attractive therapeutic target. Nevertheless, how fibroblast heterogeneity, recruitment, cell-of-origin and differential functions contribute to prostate cancer remains to be fully delineated. Developing our molecular understanding of these processes is fundamental to developing new therapies and biomarkers that can ultimately improve clinical outcomes. In this review, we explore the current challenges surrounding fibroblast identification, discuss new mechanistic insights into fibroblast functions during normal prostate tissue homeostasis and tumorigenesis, and illustrate the diverse nature of fibroblast recruitment and CAF generation. We also highlight the promise of CAF-targeted therapies for the treatment of prostate cancer.